Comparison of normal and abnormal labour by using Modified WHO Partograph - Bhatt, Manojkumar J.; Kadikar, Gunvant K.; Kanani, Medha; Shah, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Modified WHO partograph is graphical record of maternal and foetal data during progress of labour entered against time on single paper sheet. Entire labour can be interpreted in a glance on the photograph. It helps to detect abnormal progress of labour. It guides obstetrician to decide about the need for augmentation of labour or termination of pregnancy either by instrumental delivery or LSCS and avoids prolong labour before obstruction. The objectives were to study the course of normal and abnormal labour and to evaluate the maternal and perinatal outcome in normal and abnormal labour. Methods: The prospective observational hospital based study of 200 randomly selected cases coming to sir t hospital, bhavnagar for delivery during September 2016 to August 2017 was done. Progress of labour assessed by use of modified WHO partograph. Various parameters like duration of labour, mode of delivery, maternal and neonatal morbidity were studied. Results: The average duration of active first stage of labour was 4 hrs 38 mins in normal labour and 7hrs 48 mins in abnormal labour. Arrest of descent was responsible for 40% of abnormal labour. Problems like obstructed labour were avoided by timely intervention in the form of cesarean section and instrumental delivery. Maternal and perinatal outcome were satisfactory. Conclusions: Routine use of modified WHO partograph helps in early detection of abnormal course in labour. Every women in labour must be benefitted by use of modified WHO partograph for labour monitoring. It assures best maternal and perinatal outcome.